Quadratus lumborum asymmetry is not isolated to the dominant side in junior cricket fast bowlers. Issue 4 (25th May 2011) - Kountouris, Alex; Portus, Marc; Cook, Jill
Abstract : Background and aim: Bowling-side quadratus lumborum (QL) asymmetries have been previously reported on the dominant side in junior cricket fast bowlers using MRI. The aim of this study was to investigate QL asymmetry when measuring with two different methods; first using a small number of images with clear muscle borders and second using a larger number of images with less strict inclusion criteria. Methods: MRI was performed on 38 junior (14.9 years) cricket fast bowlers prior to the start of a cricket season. Each MR image slice was evaluated to determine whether the QL muscle contour was visible and was assigned an image-quality rating for inclusion in the study. The cross-sectional area of each included QL image was measured and compared with the corresponding image on the other side of the spine to determine side-to-side difference (asymmetries). Results: Using the main method of including only high-quality MR images, 25% of MR images, where QL was in the field of view, met the inclusion criteria. The mean QL asymmetry was 13%, while 55% of participants had asymmetries greater than 10%. There was no significant difference in the number of participants with dominant and non-dominant side QL asymmetry. However, there was a significant difference in the magnitude of asymmetry between the dominant side (10.5%) and non-dominant (16.4%) asymmetries. The intraclass correlation coefficient for repeated measurements of QL asymmetry for randomly selected images (18%) was excellent (ICC 0.966, 95% CI 0.89 to 0.99). Using the second measurement method, with less strict inclusion criteria for MR images, similar results on the distribution of QL asymmetry were found. Conclusion: Contrary to previous research, this study demonstrated that there was a similar distribution of QL asymmetry between the dominant and non-dominant side. The presence of only dominant side asymmetry must therefore be questioned.